Sistem Pendukung Keputusan Rekomendasi Siswa Kelas Unggulan menggunakan Metode Simple Additive Weighting (SAW) dan Weighted Product (WP) (Studi Kasus : SMA Negeri 1 Taman, Sidoarjo) - Jauhar Bariq Rachmadi; Edy Santoso; Novanto Yudistira (Jurnal Pengembangan Teknologi Informasi dan Ilmu Komputer, 2020)
Students in schools generally think about the diversity of intelligence levels, there are students who have high, ordinary, and low intelligence levels. The diversity of the intelligence levels of these students makes students who have a high level of intelligence can not maximize what they can get. Therefore the school makes a superior class program, superior classes are classes filled with students who have a high level of intelligence. The selection of superior class students in a case study in SMA Negeri 1 Taman still uses a manual that compares students with other students. So in order to simplify the selection process of superior class students, it is necessary to create a system for the recommendation process for selection of superior class program students. In carrying out the decision support system this recommendation uses the Simple Additive Weighting (SAW) and Weighted Product (WP) methods. This system uses several student grades as a criterion to be calculated including the potential academic test scores, psychological scores, and the national exam scores of each subject. The SAW method is used to calculate the overall UN score and the WP method is used to calculate all grades and rank is then taken 36 students with the largest value. From the testing that has been done, the accuracy result is 80.56%. From the results obtained it can be concluded that the use of the SAW and WP methods is quite effective in using the superior class recommendation system.